2021
DOI: 10.1007/s00338-021-02188-6
|View full text |Cite
|
Sign up to set email alerts
|

Ectohydrolytic enzyme activities of bacteria associated with Orbicella annularis coral

Abstract: Ectohydrolytic enzyme activity (EEA) potential of 37 bacterial isolates derived from Orbicella annularis coral and 2 coral pathogens (Vibrio shilonii and V. coralliilyticus) was measured as model to infer the role of bacteria in organic matter processing within coral reef ecosystems. Bacterial cell-specific activities of eight enzyme types were measured after incubation in organic matter enriched and unenriched filtered seawater. Max value of activities of alkaline phosphatase, oleate-lipase, stearate-lipase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
0
0
Order By: Relevance
“…Lipase source from deep sea can be obtained from water, marine animalium, sediments and coral environment. Coral reefs are highly biod iverse ecosystem and potential source of hydrolytic enzyme like lipase [8]. In previous studies, lipase was found to be the highest secreted enzyme from the collection of marine bacteria isolates, compared to amylase and protease [9].…”
Section: Introductionmentioning
confidence: 97%
“…Lipase source from deep sea can be obtained from water, marine animalium, sediments and coral environment. Coral reefs are highly biod iverse ecosystem and potential source of hydrolytic enzyme like lipase [8]. In previous studies, lipase was found to be the highest secreted enzyme from the collection of marine bacteria isolates, compared to amylase and protease [9].…”
Section: Introductionmentioning
confidence: 97%